Rogue & Gambit. Ring of fire - Thompson, Kelly, 1976- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2018)
Everybody's favorite X-couple is reunited! And boy, are they not happy about that ... Kitty Pryde must send Rogue and Gambit on an undercover mission to find a group of kidnapped mutants. What they discover on this mission will shock them. But will it also bring them closer together ...? It's a high-stakes adventure caper that only the two hottest X-Men can deliver!